Relation between cycling exercise capacity, fiber-type composition, and lower extremity muscle strength and muscle endurance - Segerström, A. B.; Holmbäck, A. M.; Hansson, O.; Elgzyri, T.; Eriksson, K. -F.; Ringsberg, K.; Groop, L.; Wollmer, P.; Thorsson, O. (The Journal of Strength and Conditioning Research, 2011)
The aim of the study was to determine the relation between peak oxygen uptake (Vo2peak), peak work rate (WRpeak), fiber-type composition, and lower extremity strength and endurance during a maximal incremental cycle test. Thirty-nine healthy sedentary men, aged 30-46, participated in the study. Subjects performed a maximal incremental cycle test and isokinetic knee extension (KE) and flexion (KF) strength and endurance tests at velocities of 60 and 180°/s. Muscle biopsies were taken from m. vastus lateralis and analyzed for fiber-type composition. A significant correlation existed between KE strength and Vo2peak and WRpeak. Also, KF endurance correlated significantly to Vo2peak and WRpeak. The KE endurance correlated significantly to WRpeak (rp = 0.32, p < 0.05) and almost significantly to Vo2peak (rp = 0.28, p = 0.06). Stepwise multiple regression analyses showed that KE strength, KF endurance, and the percentage of type I fibers could explain up to 40% of the variation in Vo2peak and WRpeak. The performance of sedentary subjects in a maximal incremental cycle test is highly affected by knee muscle strength and endurance. Fiber-type composition also contributes but to a smaller extent